2008
DOI: 10.3747/co.v15i6.378
|View full text |Cite
|
Sign up to set email alerts
|

The Colon Health and Life-Long Exercise Change (CHALLENGE) trial (CO.21)

Abstract: BackgroundObservational studies indicate that physical activity (pa) is strongly associated with improved disease outcomes in colon cancer survivors, but a randomized controlled trial is needed to determine whether the association is causal and whether new policies to promote exercise are justified.PurposeThe co.21 Colon Health and Life-Long Exercise Change (challenge) trial undertaken by the National Cancer Institute of Canada Clinical Trials Group (ncic ctg) is designed to determine the effects of a structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(35 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…This objective is more feasible for tertiary prevention research as demonstrated by the commencement of a large clinical trial measuring disease-free survival in colon cancer survivors during and following a 3 year exercise intervention [84]. This field of research is rapidly progressing, although the evidence for the pathways through which exercise may enhance survival is still not entirely clear.…”
Section: Future Directionsmentioning
confidence: 95%
“…This objective is more feasible for tertiary prevention research as demonstrated by the commencement of a large clinical trial measuring disease-free survival in colon cancer survivors during and following a 3 year exercise intervention [84]. This field of research is rapidly progressing, although the evidence for the pathways through which exercise may enhance survival is still not entirely clear.…”
Section: Future Directionsmentioning
confidence: 95%
“…5052 Currently, there is one ongoing intervention study to specifically study disease-free survival in stage II and III colorectal cancer survivors. 50 Courneya et al 50 endeavor to study the effect of physical activity intervention over a 3-year period, and how that intervention affected recurrences, mortality, physical functioning, quality of life, and biologic correlative markers for colon cancer patients. The study is sponsored by the National Cancer Institute of Canada and has ongoing accrual in Canada and Australia.…”
Section: Energy Balance Intervention Studies In Colorectal Cancementioning
confidence: 99%
“…• Survivors of colon cancer should be advised to engage in regular exercise, to follow the Canada Food Guide, to stop smoking, and to limit alcohol to moderate consumption (level iii) [21][22][23] .…”
Section: Questionmentioning
confidence: 99%
“…The Eastern Canadian Colorectal Cancer Consensus Conference was held in Ottawa, Ontario on October [22][23]2010. The conference is held annually, and some of the terms of reference and opening statements are taken directly from a previous publication 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation